Physical activity practice and negative self-rated health among university students during COVID-19 - Soares, Juliana de Souza; Sousa, Thiago Ferreira de; Mourão-Carvalhal, Maria Isabel Martins; Fonseca, Sandra Celina Fernandes (O Mundo da Saúde, 2025)
During the pandemic, significant changes in university students’ routines affected their lifestyle and health. This study aimed to determine the prevalence of negative self-rated health (NSRH) among university students and to analyze its association with moderate-intensity aerobic physical activity (MPA) and muscle-strengthening physical activity (MSPA) during the pandemic. A cross-sectional study was conducted with 1,150 students from Estácio de Sá University, Rio de Janeiro, with a mean age of 31.43 years (SD: 11.07), of whom 63.8% were women. Self-rated health was assessed through a single question, with “fair,” “poor,” and “very poor” considered negative responses. MPA and MSPA practices were assessed using the PERMEV instrument between August 2021 and April 2022. Descriptive analyses and binary logistic regression were performed to estimate associations, with calculation of Odds Ratios (OR) and 95% confidence intervals (95% CI), in both crude and adjusted analyses. The significance level adopted was 5%. The prevalence of NSRH was 38.6%, higher among women (42%) than men (32.5%). Increased MSPA was associated with lower odds of NSRH in both sexes, while maintaining MSPA showed an additional protective effect among men. There was a significant relationship between MSPA and NSRH in both sexes during the pandemic, suggesting that MSPA may reduce negative impacts on health perception during prolonged crisis periods, highlighting the importance of strategies to encourage this type of exercise in situations of physical and social distancing.